Analysis of UMKM Taxpayer Compliance in Rural Areas of Semarang Regency: Case Study of Government Regulation (PP) 23 of 2018 - Widiarto, Tri; Sugiyanto, Sugiyanto (Cognitionis Civitatis et Politicae, 2025)
This study analyzes the tax compliance of MSMEs in rural areas of Semarang Regency regarding the implementation of Government Regulation 23/2018. Using a qualitative approach, this research involved interviews and observations of 30 MSME owners. Data shows that out of 24,567 MSMEs, only 45% are registered as taxpayers with a tax return reporting compliance rate of 62.3%. Factors affecting tax compliance include geographical distance, income level, digital literacy, and seasonal income patterns. MSMEs located more than 20 kilometers from the tax office have 23% lower compliance rates, while 65% of MSME owners are unfamiliar with online tax reporting systems. The findings indicate the need for an integrated approach to improving MSME tax compliance in rural areas, including strengthening socialization, increasing service accessibility, and developing adaptive taxation systems.